2021
DOI: 10.48162/rev.39.021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sugarcane straw on weed germination control

Abstract: This research studied the effectiveness of herbicide treatments in weed control and during different periods of emergence, when applied to varying amounts of straw. The experiment was conducted in a greenhouse with pre-emergent herbicides: amicarbazone, metribuzin, indaziflam, isoxaflutole, amicarbazone + indaziflam, metribuzin + indaziflam, and isoxaflutole + indaziflam, against three species (Sorghum halepense, Rottboellia exaltata, and Mucuna aterrima). The experimental design was completely randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…During the initial evaluation period in our study, the low control percentage of both weeds, mainly in the association of umioxazin and diclosulan treatment, is related to the low soil moisture during the rst 7 days after application (Fig. 1), so that to achieve the herbicide bioavailability in the soil solution, soil moisture is necessary in the rst week after application (Silva et al 2021). On the other hand, when there is high soil moisture, the umioxazin provides satisfactory weed control (Correia et al 2013).…”
Section: )mentioning
confidence: 85%
See 4 more Smart Citations
“…During the initial evaluation period in our study, the low control percentage of both weeds, mainly in the association of umioxazin and diclosulan treatment, is related to the low soil moisture during the rst 7 days after application (Fig. 1), so that to achieve the herbicide bioavailability in the soil solution, soil moisture is necessary in the rst week after application (Silva et al 2021). On the other hand, when there is high soil moisture, the umioxazin provides satisfactory weed control (Correia et al 2013).…”
Section: )mentioning
confidence: 85%
“…Rodrigues et al (2022) stated that R. exaltata was controlled by the herbicide indazi am at dosages of 75, 150, and 225 mL in pre-emergence, as the control percentages remained high (above 91%) after 84 DAA compared with the control treatment, a fact that expresses the long residual effect of indazi am (Rodrigues et al 2022). Control of R. exaltata by isolated indazi am, in the emergence periods at 0, 30, and 60 DAT was over 80% in ratoon cane (Silva et al 2021). The results obtained by Silva et al (2021) indicated that the isolated application of indazi am achieves better control over monocotyledonous species than over eudicot ones.…”
Section: )mentioning
confidence: 92%
See 3 more Smart Citations